Biobased PLA/NR-PMMA TPV with balanced stiffness-toughness: In-situ interfacial compatibilization, performance and toughening model. (January 2020) - Wang, Wentao; Huang, Jiarong; Gong, Zhou; Fan, Jianfeng; Cao, Liming; Chen, Yukun
Abstract: Using rubber to toughen polylactide (PLA) is always accompanied by the sharp reduction in stiffness. Herein, PLA/poly (methyl methacrylate) grafted natural rubber (NR-PMMA) thermoplastic vulcanizates (TPVs) with balanced stiffness-toughness were fabricated. With the addition of 40 wt % NR-PMMA, the impact strength and tensile toughness of PLA/NR-PMMA TPV significantly improved to about 102.7 kJ/m 2 and 66.1 MJ/m 3, respectively, compared with those of 2.7 kJ/m 2 and 2.4 MJ/m 3 for the pure PLA. Meanwhile, the yielding stress was maintained at 34.5 MPa. Fourier transform infrared spectroscopy (FTIR) confirmed the formation of in-situ interfacial compatibilization between PLA and rubber phases. Both tensile and impact toughening mechanism were studied and deduced as considerable energy dissipation provided by the continuous rubber phase. Instrumented notched impact tests demonstrated that the energy dissipating in crack propagation process contributed to the main part of impact toughness. In addition, a novel toughening model based on bicontinuous structure was incorporated, which showed good applicability in predicting the impact strength of PLA/NR-PMMA TPVs. Graphical abstract: Image 1 Highlights: PLA/NR-PMMA binary TPVs with co-continuous phase morphology were prepared. In-situ situ compatibilization between plastic and rubber phases was realized. Balanced stiffness-toughness of the TPVs was achieved. A novel toughening model was introduced and showed good precision on predicting impact strength. All the materials used in this work are biobased and sustainable.